2022
DOI: 10.2478/ata-2022-0019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the New Digital Side Mirror Technology from Driver’s Subjective Point of View Considering Traffic Safety

Abstract: The automotive industry is experiencing an era of technological innovations from conventional passenger cars, trucks to agricultural machinery. Digital side mirror technology is one of the latest topics in the field of advanced driver assistance systems which is developing rapidly. This study evaluates the applicability of digital side mirror technology in the car interior, based on drivers’ feedbacks. The research was conducted in the form of a questionnaire to determine the drivers’ reactions and affinity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It has been shown that the use of digital mirror technology can have a direct negative effect on road safety, especially in combination with other negative effects given by the technical nature of the technology under investigation, such as image latency in digital displays. These negative phenomena can further be combined with the driver´s attitude, given by his cognitive functions (Babu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that the use of digital mirror technology can have a direct negative effect on road safety, especially in combination with other negative effects given by the technical nature of the technology under investigation, such as image latency in digital displays. These negative phenomena can further be combined with the driver´s attitude, given by his cognitive functions (Babu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated and prolonged forced visual accommodation can lead to a deterioration of accommodative amplitude (Sullivan, 2008). The need to use visual accommodation is one of the essential differences between conventional rear-view mirrors and digital rear-view mirrors (Babu et al, 2022). Due to the physical nature of the optical system, it is not necessary to use visual accommodation with conventional rear-view mirrors, and the driver basically always focuses on the same distance (practically to infinity).…”
Section: Equipment Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, these systems can provide features such as distance measurement, object detection, and warning systems that can improve safety and reduce the risk of accidents [21,22]. Moreover, depending on the design, CBMSs may be more aerodynamically efficient than traditional mirrors, which can improve fuel efficiency and reduce emissions [23,24,31]. Furthermore, these systems can be more compact and less obtrusive than traditional mirrors, which can improve the aesthetic appeal of vehicles and reduce wind noise [24].…”
Section: Previous Testing Found In the Literaturementioning
confidence: 99%